Utility of dual-energy contrast-enhanced spectral mammography for the diagnosis of multicentric breast cancer - A. V. Chyornaya; R. Kh. Ulyanova; P. V. Krivorotko; A. S. Artemyeva; S. S. Bagnenko; E. K. Zhiltsova; S. N. Novikov; V. V. Danilov; P. I. Krzhivitskiy; V. F. Semiglazov (ABV-press, 2022)
Background. Breast cancer (BC) can be unifocal, multifocal, multicentric (MCBC) and bilateral according to number and localization of tumors. MCBC has different clinical and biological characteristics compared to unifocal BC, for example, a higher risk of lymph node involvement, a more aggressive natural history and a worse prognosis. Therefore, accurate diagnosis and detection of MCBC is one of the main tasks of imaging.Objective: to compare diagnostic accuracy of contrast enhanced spectral mammography (CESM) and digital mammography (DM) in the diagnosis of MCBC.Materials and methods. The study included 438 women with suspected BC. The results of DM and CESM were compared with the results of a pathomorphological study performed after surgery or biopsy to assess the effectiveness of imaging modalities. DM was performed for all women using a Senographe DS (GE, USA) unit. CESM was performed after intravenous injection of non-ionic contrast agents using injector with breast compression in the craniocaudal and mediolateral projections. The study was performed for both glands regardless of the location of the suspicious lesion in order to timely diagnose clinically asymptomatic bilateral cancer. The final diagnosis was made based on the results of the pathomorphological examination. MCBC was diagnosed when two or more tumors at a distance of 3 cm or more from each other were detected. Visualization of additional grouped calcifications of malignant type occupying a small portion of breast tissue (more than 15 pieces per 1 sq. cm) was considered as another mammographic sign of MCBC.Results. According to the pathomorphological examination BC was diagnosed in 154 (35 %) women out of 438 examined patients. MCBC was identified in 25 (16 %) of 154 patients. CESM was more effective than DM in detecting MCBC with sensitivity of 88.0 % vs 48.0 % (p = 0.002), accuracy of 92.2 % vs 90.9 %, negative predictive value of 97.6 % vs 90.8 % (p = 0.02), respectively. But the specificity was significantly higher in DM than in CESM - 99.2 % vs 93.0 % (p = 0.009), respectively, and the positive predictive value did not differ significantly (p = 0.12).Conclusion. CESM is a more sensitive method for diagnosing MCBC compared to DM with sensitivity of 88.0 % vs 48.0 %. The high negative predictive value of CESM (97.6 %) confirms the fact that this modality is an effective method for planning surgery and radiation therapy.